Cryopreservation of Animal’s Erythrocytes under Dimethyl Sulfoxide, Polyethylene Oxide and Glycerol Protection - Denisova, O. N.; Zhegunov, G. F.; Babijchuk, L. A. (Problems of Cryobiology and Cryomedicine, 2005)
Researches on cryopreservation of equine, bovine and canine erythrocytes with penetrative and non-penetrative cryoprotectants were carried-out. DMSO and PEO-1500 were revealed to be quite efficient for erythrocyte cryopreservation of animals under study.